Akad Murabahah dalam Islam - Ikbal, Muhammad; Chaliddin, Chaliddin (Department of Islamic Economic Law, Faculty of Sharia, Sultanah Nahrasiyah State Islamic University, Lhokseumawe, 2022)
Buying and selling activities in everyday life is a phenomenon that has become a habit of the community. Especially the Indonesian people, especially the Indonesian people who work as traders. Buying and selling is regulated in Islamic sharia, but the knowledge of the people who buy and sell is still lacking. One of the contracts that often occurs in the community is the murabahah contract. Murabahah is a sale and purchase agreement between the bank and the customer. Islamic banks buy goods needed by customers and then sell them to the customer concerned at the acquisition price plus a profit margin agreed between the Islamic bank and the customer.